Transboundary WEF nexus analysis: a case study of the Songwe River Basin - Masia, S.; Susnik, J.; Jewitt, G.; Kiala, Z.; Mabhaudhi, Tafadzwanashe (Elsevier, 2022)
Over the past decade, the water, energy, and food (WEF) nexus approach has evolved to become a focus of the Southern African Development Community (SADC) development strategies. However, a lack of empirical evidence, appropriate methods, and qualitative and quantitative tools to implement the WEF nexus approach has been highlighted. This chapter describes the application of the WEF nexus approach in the Songwe River Basin (SRB) located on the border between Malawi and Tanzania as a demonstration of how this lack of evidence and tools is starting to be addressed. The basin is currently facing rapid population growth, which is leading to a considerable increase in resource demand and environmental issues and has been identified as a priority basin for SADC. The SRB Development Programme (SRBDP) includes several projects that collectively aim to improve the environmental and socioeconomic status of the basin. The integrated approach proposed to assess the SRBDP's expected outcomes through a WEF nexus lens is based on the development and application of qualitative and quantitative tools that support decision-makers to assess feasible sustainable development pathways in the basin, and more broadly in the SADC region. This chapter focuses on the qualitative analysis of the WEF nexus system and explains the process of identifying the major sectors and subsectors involved in the SRBDP, the main interlinkages between them, and potential synergies and trade-offs assessing how decisions made in a sector may influence others. The qualitative analysis of the SRB shows that although the projects included in the SRBDP are expected to have positive impacts on the environment and the socioeconomic system of the basin, downsides that may have an impact on human and ecosystem health are also possible. Early identification of such issues can help to limit detrimental impacts in the future. In the analysis, potential Sustainable Development Goals (SDGs), objectives, and indicators that may be addressed in the SRB are identified, highlighting the importance of applying the holistic approach to enhance and boost the achievement of SDGs in the basin.